2019
DOI: 10.1098/rsbl.2019.0198
|View full text |Cite|
|
Sign up to set email alerts
|

Obligately silent males sire more offspring than singers in a rapidly evolving cricket population

Abstract: How sexual traits are gained and lost in the wild remains an important question in evolutionary biology. Pacific field crickets ( Teleogryllus oceanicus ) in Hawaii provide an unprecedented opportunity to investigate the factors facilitating evolutionary loss of a sexual signal in real time. Natural selection from an acoustically orienting parasitoid fly drove rapid evolution of a novel, silent male morph. While silent (flatwing) males enjoy protection from the fly, they face difficulty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Kauai males show a similar pattern of reproductive tissue investment associated with the wing mutation, where normal‐wing males possess heavier testes than flatwing males (Bailey et al., ; Rayner et al., ). Kauai males also exhibit an inconsistency between potential and actual reproductive outcomes, as flatwing males sire more offspring than normal‐wings when mated to a normal‐wing female (Heinen‐Kay et al., ). At present, the mechanism underlying this discrepancy is unclear in both males and females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kauai males show a similar pattern of reproductive tissue investment associated with the wing mutation, where normal‐wing males possess heavier testes than flatwing males (Bailey et al., ; Rayner et al., ). Kauai males also exhibit an inconsistency between potential and actual reproductive outcomes, as flatwing males sire more offspring than normal‐wings when mated to a normal‐wing female (Heinen‐Kay et al., ). At present, the mechanism underlying this discrepancy is unclear in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Social exposure to sexual signals is also known to influence reproductive physiology in male crickets. Male T. oceanicus raised in the absence of calling song, mimicking a population with high density of flatwing males or few competitors, invested less in testes size (Bailey et al., ) and exhibit lower sperm viability (Gray & Simmons, ), although acoustic experience does not appear to affect male reproductive success (Heinen‐Kay et al., ). Most studies have found that female crickets reared in the absence of song show reduced investment in reproductive tissues (Bateman, Verburgt, & Ferguson, ; Conroy & Roff, ; Kasumovic, Chen, & Wilkins, ; Kasumovic, Hall, Try, & Brooks, ; Rebar, Barbosa, & Greenfield, ), similar to males, while one study showed no effect of acoustic experience on egg laying (Lierheimer & Tinghitella, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flatwing males also possess a reproductive advantage and sire more offspring than normal‐wings per successful mating event (Heinen‐Kay et al. 2019b). However, silent males face major precopulatory barriers to mating because they cannot sing, and normal‐wing males are favored by sexual selection (Tanner et al.…”
mentioning
confidence: 99%
“…Studies that have decoupled courtship song from male wing morph show that females are less likely to mate in the absence of courtship song, and do not discriminate between males based solely on their wing morph (Heinen‐Kay et al. 2019b; Kota et al. unpubl.…”
mentioning
confidence: 99%